2016
DOI: 10.1097/lgt.0000000000000207
|View full text |Cite
|
Sign up to set email alerts
|

mHealth to Train Community Health Nurses in Visual Inspection With Acetic Acid for Cervical Cancer Screening in Ghana

Abstract: Objectives There is a shortage of trained healthcare personnel for cervical cancer screening in low/middle income countries. We evaluated the feasibility and limited efficacy of a smartphone-based training of community health nurses in Visual Inspection of the cervix under Acetic Acid (VIA). Methods During April-July of 2015 in urban Ghana, we designed and developed a study to determine the feasibility and efficacy of an mHealth supported training of community health nurses (CHNs) (n=15) to perform VIA and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 11 publications
0
87
0
Order By: Relevance
“…Our study though conducted with fidelity had some limitations. First of all, we believe that real‐time feedback from expert would have improved skill retention for the nurse (Asgary et al., ). Moreover, a setup for telemedicine for such distant centers can help overcome the issue of image sharing and early feedback (within 24 hr).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study though conducted with fidelity had some limitations. First of all, we believe that real‐time feedback from expert would have improved skill retention for the nurse (Asgary et al., ). Moreover, a setup for telemedicine for such distant centers can help overcome the issue of image sharing and early feedback (within 24 hr).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were images which the expert could not assess for screening decision. Technical training in photography skills or better imaging devices could fill this gap (Asgary et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include inconsistencies in the kinds of smartphones used by community healthcare workers that lead to poor imaging of the condition, which in turn, causes difficulties in assessing and diagnosing patients (Asgary et al, 2016;Free et al, 2013). Additionally, a systematic review of mHealth interventions on community healthcare workers found that most interventions were overwhelmingly focused on the context of the global North, with many of them having limited success outside of that space (Free et al, 2013).…”
Section: Mhealth and Communitymentioning
confidence: 99%